The first Australian gravimetric quasigeoid model with location-specific uncertainty estimates - Featherstone, Will; McCubbine, Jack; Brown, N.; Claessens, Sten; Filmer, Michael; Kirby, Jon (Springer - Verlag, 2018)
We describe the computation of the first Australian quasigeoid model to include error estimates as a function of location that have been propagated from uncertainties in the EGM2008 global model, land and altimeter-derived gravity anomalies and terrain corrections. The model has been extended to include Australia’s offshore territories and maritime boundaries using newer datasets comprising an additional (Formula presented.)280,000 land gravity observations, a newer altimeter-derived marine gravity anomaly grid, and terrain corrections at (Formula presented.) resolution. The error propagation uses a remove–restore approach, where the EGM2008 quasigeoid and gravity anomaly error grids are augmented by errors propagated through a modified Stokes integral from the errors in the altimeter gravity anomalies, land gravity observations and terrain corrections. The gravimetric quasigeoid errors (one sigma) are 50–60 mm across most of the Australian landmass, increasing to (Formula presented.) mm in regions of steep horizontal gravity gradients or the mountains, and are commensurate with external estimates.